Every hill has its leopard: patterns of space use by leopards (Panthera pardus) in a mixed use landscape in India - Sanjay Gubbi; Koustubh Sharma; Vijaya Kumara (PeerJ, 2020)
Understanding abundance and distribution of species is often necessary for wildlife conservation. However, elusive species such as the leopard (Panthera pardus) that have wide geographical distribution and typically low abundance pose a constant challenge to conservationists due to logistical and methodological constraints. Although leopard abundance has been estimated at the scale of protected areas or other smaller regions, reliable information describing leopard distribution over large spatial scales remains largely unavailable. Knowledge about space use by leopards within landscapes could help improve conservation management, reduce human-wildlife conflict, and also facilitate population status monitoring. We carried out occupancy surveys across c. 24,000 km2 in southern India in a landscape that consisted a mosaic of leopards’ natural habitats and highly human-dominated areas. We investigated the effects of key ecological and anthropogenic variables in determining leopard space use patterns. We addressed imperfect detections obtained using sign surveys conducted on spatially replicated transects within sampling units by modeling detection as a function of spatial auto-correlation and covariates. Our results show that the probability of site-use by leopards across the landscape varied between 0.02 (95% CI [0.01–0.09]) and 0.99 (95% CI [0.99–1.0]) across the study area. The best model (AIC weight = 0.97) showed that the probability of leopard space use was affected by the proportion of natural habitats and the presence of large wild prey in the sampling unit. Given that India is undergoing rapid modifications due to economic changes and demand for natural resources, we emphasize the need for landscape-based approach for conserving and monitoring leopards. We argue that leopards are an indicator of functional ecosystems represented by scrub, deciduous forest and rocky outcrops that do not always get prioritized for conservation, unlike densely forested habitats. Similarly, conservation of natural large wild prey, especially outside the protected area system, should assume greater importance, which could also have a positive impact on reducing human-leopard conflict.